Analyse comparative des traductions des noms abstraits pluralisés dans les textes littéraires (sur la base des oeuvres de Françoise Sagan) - Piskozub, Zoriana (2022)
Modern linguistic research focuses on phenomena that simultaneously affect different branches of science. Abstractnouns, which lie at the intersection of language, speech and thought and a person’s unique ability to generalize, areexamples of exactly such phenomena. The grammatical form of the plural, which is a structural basis of language,is increasingly prevalent in the general grammatical theory of language development. The meaning of abstractvocabulary and its plural forms poses researchers with questions that are not always unambiguous: what are therelations of words in a sentence, how do they agree, and what is the participation of the plural in the formationof new lexical meanings and new plural words. The article is devoted to these issues, as well as to the comparativeanalysis of abstract plural nouns in modern French and Ukrainian. We review the peculiarities of the functioning ofabstract plural nouns in typologically dissimilar languages (analytically-inflected French and synthetically-inflecteUkrainian). We also analyse the semantic transformations of abstract substantives, and we illustrate on a specifilanguage material their potential ability to convey expressiveness in artistic speech. Examples from literature havemade it possible to consider the semantic alterations of abstract plural nouns and, in particular, the number ofabstract nouns which appear as the dominant of their semantic modifications. The analysis of works of fiction byFrench authors, most notably, Françoise Sagan, and their Ukrainian translations, helped to identify the uniquenessof the functioning of singular and plural forms of abstract nouns.
Keywords: abstract plural nouns; comparative analysis; number category; artistic speech